Eugenol embedded zein and poly(lactic acid) film as active food packaging: Formation, characterization, and antimicrobial effects. (1st August 2022) - Huang, Xueying; Ge, Xiaohan; Zhou, Liping; Wang, Yi
Highlights: Zein and poly(lactic acid) (PLA) were blended to make biodegradable packaging. Polyethylene glycol and eugenol were used as plasticizer and antimicrobial agent. Mechanical, water and gas barrier properties of zein films were largely improved. Eugenol added films showed similar antimicrobial effects as pure eugenol. Abstract: Biodegradable packaging is more eco-friendly compared with the synthetic plastics. To improve the physical properties of the zein films, poly(lactic acid) (PLA) was mixed with zein to make a biodegradable blend film. The composition of the film with the best properties was the one with zein and PLA in the mass ratio of 1:1 with the addition of 20% poly(ethylene glycol) as the plasticizer. The incorporation of PLA significantly increased the elongation, reduced the tensile strength, and decreased the water vapor and gas permeabilities of zein films. The antimicrobial agent eugenol added in the film significantly inhibited the growth of both S. aureus and E. coli . The migration tests were conducted to confirm the safety of the blend films. This is the first-time report of zein-PLA blend film. The antimicrobial zein-PLA-eugenol film with enhanced mechanical and barrier properties has a high potential as active biodegradable food packaging.